International Science and Technology - Mtewa, Mekki. author. aut Link
XV, 201 p.
Keywords: This book formulates both a theory of science and technology, a philosophy guiding its development and utilization as well as foundations for developing a policy on science and technology. The book should enrich debate and future searches for the paradigm in international science and technology.